µID-TIMS: spatially resolved high-precision U–Pb zircon geochronology - S. Markovic; J.-F. Wotzlaw; D. Szymanowski; J. Reuteler; P. Zeng; C. Chelle-Michou (Geochronology)
We present a novel methodology for spatially resolved high-precision U–Pb geochronology of individual growth domains in complex zircon. Our approach utilizes a multi-ion-species (Xe+/Ar+<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="44pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="08617a421c2c1c3d6f2ee873ebddf585"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="gchron-6-621-2024-ie00001.svg" width="44pt" height="14pt" src="gchron-6-621-2024-ie00001.png"/></svg:svg>) plasma focused ion beam (PFIB)–femtosecond (fs) laser system equipped with a scanning electron microscope (SEM). This system enables micrometer-resolution sampling of zircon growth domains with real-time monitoring by cathodoluminescence SEM imaging. Microsamples are then extracted, chemically abraded, dissolved, and analyzed by isotope dilution thermal ionization mass spectrometry (ID-TIMS) to obtain high-precision U–Pb dates. For its superior beam precision (∼ 8–20 µm diameter), cleaner cuts, and negligible nanometer-scale damage imparted on the zircon structure, PFIB machining (30 kV) is preferred for microsamples of sizes expected in most future studies focusing on texturally complex natural zircon (20–120 µm length scales). Femtosecond laser machining is significantly faster and therefore more appropriate for larger microsamples (>120 µm length scales), but it is also coarser (≥20 µm probe size), produces rougher cuts, and creates a micrometer-scale-wide structurally damaged zone along the laser cuts (i.e., 2 orders of magnitude wider compared to PFIB). Our experiments show that PFIB machining can be conducted on zircon coated with carbon and protective metal coatings as neither offset the U–Pb systematics, nor do they introduce trace amounts of common Pb. We used a Xe+ PFIB and femtosecond laser to obtain U–Pb dates for Mud Tank and GZ7 zircon microsamples covering a range of sizes (40 × 18 × 40–100 × 80 × 70 µm) and found that microsampling does not bias the accuracy of the resulting µID-TIMS U–Pb dates. The accuracy and precision of µID-TIMS dates for zircon of any given age depend, as for non-microsampled zircon, on the available mass of U and radiogenic Pb – both a function of sample size. Our accompanying open-source code can aid researchers in estimating the necessary microsample size needed to obtain accurate dates at precision sufficient to resolve the processes under study. µID-TIMS bridges the gap between conventional bulk-grain high-precision dating and high-spatial-resolution in situ techniques, enabling the study of the timescales of a variety of processes recorded on the scale of individual growth zones in zircon. This method can be applied to zircon of any age and composition, from terrestrial systems to precious samples from other planetary bodies.